Transfer of antibiotic resistance from manure-amended soils to vegetable microbiomes. (September 2019) - Zhang, Yu-Jing; Hu, Hang-Wei; Chen, Qing-Lin; Singh, Brajesh K.; Yan, Hui; Chen, Deli; He, Ji-Zheng
Abstract: The increasing antimicrobial resistance in manure-amended soil can potentially enter food chain, representing an important vehicle for antibiotic resistance genes (ARGs) transmission into human microbiome. However, the pathways for transmission of ARGs from soil to plant remain unclear. Here, we explored the impacts of poultry and cattle manure application on the patterns of resistome in soil and lettuce microbiome including rhizosphere, root endosphere, leaf endosphere and phyllosphere, to identify the potential transmission routes of ARGs in the soil-plant system. After 90 days of cultivation, a total of 144 ARGs were detected in all samples using high-throughput quantitative PCR. Rhizosphere soil samples harbored the most diverse ARGs compared with other components of lettuce. Cattle manure application increased the abundance of ARGs in root endophyte, while poultry manure application increased ARGs in rhizosphere, root endophyte and phyllosphere, suggesting that poultry manure may have a stronger impact on lettuce resistomes. The ARG profiles were significantly correlated with the bacterial community, and the enrichment of soil and plant resistomes was strongly affected by the bacterial taxa including Solibacteres, Chloroflexi, Acidobacteria, Gemm-1 and Gemmatimonadetes, as revealed by the network analyses. Moreover, the overlaps of ARGs between lettuce tissues and soil were identified, which indicated that plant and environmental resistomes are interconnected. Our findings provide insights into the transmission routes of ARGs from manured soil to vegetables, and highlight the potential risks of plant resistome migration to the human food chain. Graphical abstract: Unlabelled Image Highlights: We established a glasshouse experiment to explore the transmission pathways of ARGs in the plant-soil system. Diverse ARGs were detected in soil and lettuce microbiomes. Poultry manure application significantly increased the ARG abundance in root endophyte and phyllosphere of lettuce. Two transmission routes of ARGs are proposed by identifying the shared resistome between manured soils and lettuce.